2019
DOI: 10.1051/0004-6361/201935813
|View full text |Cite
|
Sign up to set email alerts
|

The most massive, passive, and oldest galaxies at 0.5 < z < 2.1: Downsizing signature from galaxies selected from MgUV index

Abstract: Aims. We seek is to identify old and massive galaxies at 0.5 Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…Correspondingly, the peak CSFH of each mass bin reduces with reducing stellar mass, as reflected by the decline of the total CSFH in the past 10 Gyr. This is entirely consistent with the "downsizing" paradigm, which suggests that more massive galaxies formed their stars earlier (Cowie et al 1996;Cimatti et al 2006;Thomas et al 2019). This trend is qualitatively similar to that found by Heavens et al (2004) in their fossil analysis of SDSS galaxies.…”
Section: Stellar Mass Trendssupporting
confidence: 80%
“…Correspondingly, the peak CSFH of each mass bin reduces with reducing stellar mass, as reflected by the decline of the total CSFH in the past 10 Gyr. This is entirely consistent with the "downsizing" paradigm, which suggests that more massive galaxies formed their stars earlier (Cowie et al 1996;Cimatti et al 2006;Thomas et al 2019). This trend is qualitatively similar to that found by Heavens et al (2004) in their fossil analysis of SDSS galaxies.…”
Section: Stellar Mass Trendssupporting
confidence: 80%
“…The studies based on semi-analytic galaxy formation models (e.g., Kauffmann et al 1993;Baugh et al 1996;De Lucia et al 2006;De Lucia & Blaizot 2007;Neistein et al 2006;Guo & White 2008;Parry et al 2009;Lee & Yi 2013) and hydrodynamical simulations (e.g., Oser et al 2010;Lackner et al 2012;Qu et al 2017;Rodriguez-Gomez et al 2016) show that the low-redshift massive galaxies may form most of stellar masses in their progenitor galaxies at high redshifts through in-situ star formation (50 per cent at z ∼ 5; De Lucia & Blaizot (2007)), and then assemble through galaxy mergers later (e.g., Rong et al 2018). This formation scenario can explain the observational results that the most massive galaxies appear to have a large number of older stellar FONDECYT postdoctoral fellow populations (e.g., Bower et al 1992;Cowie et al 1996;Heavens et al 2004;Cimatti et al 2004;Glazebrook et al 2004;Gallazzi et al 2005;Thomas et al 2019), and higher α-element enhancement/shorter star-formation timescales (e.g., Thomas et al 2010;Johansson et al 2012;Zheng et al 2019), which is referred to as 'downsizing' effect. However, the observational surveys (e.g., Mobasher et al 2005;Wiklind et al 2008) have also found a significant population of massive galaxies at high redshifts (z > 2), supporting a drastic stellar mass growth in these galaxies at early epochs.…”
Section: Introductionmentioning
confidence: 91%
“…Stellar age is one of the most important galaxy physical parameters, but at the same time, one of the most difficult to estimate correctly (e.g. Siudek et al 2017 ;Thomas et al 2019 ). There are a number of definitions and methodologies for how to derive stellar ages.…”
Section: Stellar a G Es Of The Red Nugget Samplementioning
confidence: 99%